Testing Cyclic Fatigue Resistance of Nickel Titanium Rotary Endodontic Instruments: A Validation Study for a Minimum Quality Criterion in a Standardized Environment - Peters, Ove A.; Chien, Philip Y.-H.; Armitt, Keryl; Macorra, Jose C.; Arias, Ana (Frontiers in Dental Medicine, 2021)
Introduction: Cyclic fatigue resistance of rotary endodontic instruments has been extensively studied in the last two decades, yet with no standardization. While new low-cost instruments are now manufactured, a standard is lacking to guarantee a minimum quality. This study aimed to validate a new model for CF testing through a fixture proposed for ISO Specification 3630-1 and to establish a minimum quality standard based on testing conditions and material characteristics. Materials and methods: Size 25/0.06 instruments of ProFile Vortex (PF) and Vortex Blue (VB) were run until failure in curved metallic fixtures (5 or 7.5 mm radius) built according to a proposal for an additional test for the ISO 3630-1 standard. High resolution videos were recorded, number of cycles to failure (NCF) registered and apical fragments measured with a digital caliper. Surface strain was determined from test dimensions and fragment lengths. Mean life, β and η parameters were calculated with Weibull analysis. NCF data were compared using student's t-tests and referenced to a minimum required cycles at fracture (Cmin) based on austenite finish temperatures, testing temperature and deformation. Results: VB instruments were statistically more resistant than PF in both 7.5 mm radius curve (p = 0.001) and 5 mm radius curve (p = 0.002) simulated canals. Weibull probability plots showed higher mean life for VB than PV. NCF for both instruments were higher than Cmin. Conclusions: The NCF results in this study support the findings of previous studies where VB and PF were compared. The novel test design appears a suitable addition to ISO 3630-1.